PENGEMBANGAN FARM CYCLING SEBAGAI STRATEGI AGROWISATA DI DESA PITRA, TABANAN - Indrawati, Yayu; Wulandani, Ni Luh Kadek Laksmi; Dewi, LGLK.; Andre Putra Pratama, I Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 12 No 2 (2024): Jurnal IPTA (December 2024)DO - 10.24843/IPTA.2024.v12.i02.p20, 2025)
As a village surrounded by famous tourist destinations in Tabanan, Pitra Village has not yet developed its village in the tourism sector. The aim of this research is to find out and map the existing tourism potential and to directly assist in developing tourism in this village by observing the 4A components (Attractions, Accessibilities, Amenities, and Ancillaries). This is a qualitative research with asset based community development (ABCD)  approach. The data collected by interview, observation, and literature study. The results show, Pitra Village has a good accessibility, varied attractions, and adequate amenities. One thing that it doesn't have is the ancillary aspect. Dominated with agricultural land, Pitra Village is very suitable to be developed as an agritourism destination. In this early stage, working farm passive contact activity and working farm indirect contact agritourism types are very applicable to be developed. The output of this research is that cycling and trekking trails were created. An online information regarding these trails is provided as well in the form of barcodes that are installed along the trails to help tourists enjoy the right track.